The effector NlOBP1b from the brown planthopper suppresses rice immunity by manipulating the OsCK2 complex - Chao Wang; Can Wei; Chang-Lai Qiu; Supaporn Falert; Yong-Qian Zhang; Shi-Yu Yu; Man-Qun Wang (Proceedings of the National Academy of Sciences, 2026)
Odorant-binding proteins (OBPs) are crucial mediators in the peripheral olfactory perception of insects, functioning as a link between the external environment and odor receptors. Recent research has revealed their noncanonical role as salivary proteins that mediate plant–herbivore interactions, though the underlying mechanisms remain poorly understood. This study investigates the molecular basis of NlOBP1b, a salivary effector protein in the brown planthopper ( Nilaparvata lugens , BPH), which suppresses plant immune responses and enhances insect fitness. NlOBP1b -RNAi BPH results in reduced adaptability to host plants. Furthermore, NlOBP1b specifically interacts with the regulatory subunits of casein kinase II, OsCK2β3 and OsCK2β4. On one hand, NlOBP1b disrupts the assembly of the OsCK2β3–OsCK2α2 holoenzyme complex; on the other hand, it competes with the bZIP superfamily transcription factor OsTGA5 for binding to the OsCK2β4–OsCK2α2 complex, results suppressing holoenzyme-mediated phosphorylation and transcriptional activity of OsTGA5, ultimately reducing lignin accumulation. This disruption undermines the defense mechanisms of rice and significantly enhances the adaptability of BPH to its host.